American security and the global war on terror - Jacob, Edwin Daniel (Emerging technologies, ethics and international affairs, 2020)
"This book delivers an interpretive framework for making sense of today's geopolitical landscape and illustrates the impact ideology has had on American foreign policy. Casting new light on the impact ideology and technology have had on contemporary security practices, Jacob finds that America's security practices in the global "war on terror" have been guided by Cold War logic that has subordinated strategy to tactics. It shows that deep-rooted prejudices and presuppositions regarding American exceptionalism have had a disastrous impact on the policies of the United States, not only in dealing with terrorism, but also in seeking to impose American hegemony in the Middle East. The result of this "post-strategic" outlook is to increase insecurity as practices, from rendition and torture to preemptive strikes and nation building to drones and assassinations, show the insoluble link between ethics and security. This book offers a new model for dealing with security issues and a new perspective on foreign policy that highlights the need for order, predictability and stability"--